The Influence of Social Media Content, Price, and Product Quality on Consumer Buying Interest in Fitri Aisyah Perfume - Shindi Harnoni; Aulia Indra; Raja Saul Marto Hendry (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the influence of social media content, price, and product quality on consumer buying interest in Fitri Aisyah Parfume. The independent variables in this study are social media content, price, and product quality, while the dependent variable is consumer buying interest. This study uses a quantitative approach with a survey method. The sampling technique used purposive sampling with a total of 96 respondents who had seen or bought Fitri Aisyah Parfume products. Data were collected through questionnaire deployment and analyzed using multiple linear regression with a significance rate of 5%. The results of the study show that partially social media content, price, and product quality have a positive and significant effect on consumer buying interest. Simultaneously, these three variables also have a significant effect on buying interest. Product quality variables have the most dominant influence in increasing consumer buying interest. These findings indicate that a social media-based marketing strategy supported by appropriate pricing and good product quality can optimally increase consumer buying interest.